White-nose syndrome without borders: Pseudogymnoascus destructans infection tolerated in Europe and Palearctic Asia but not in North America - Zukal, Jan; Bandouchova, Hana; Brichta, Jiri; Cmokova, Adela; Jaron, Kamil S; Kolarik, Miroslav; Kovacova, Veronika; Kubátová, Alena; Nováková, Alena; Orlov, Oleg; Pikula, Jiri; Presetnik, Primož; et al. (Scientific reports, 2016)
A striking feature of white-nose syndrome, a fungal infection of hibernating bats, is the difference in infection outcome between North America and Europe. Here we show high WNS prevalence both in Europe and on the West Siberian Plain in Asia. Palearctic bat communities tolerate similar fungal loads of Pseudogymnoascus destructans infection as their Nearctic counterparts and histopathology indicates equal focal skin tissue invasiveness pathognomonic for WNS lesions. Fungal load positively correlates with disease intensity and it reaches highest values at intermediate latitudes. Prevalence and fungal load dynamics in Palearctic bats remained persistent and high between 2012 and 2014. Dominant haplotypes of five genes are widespread in North America, Europe and Asia, expanding the source region of white-nose syndrome to non-European hibernacula. Our data provides evidence for both endemicity and tolerance to this persistent virulent fungus in the Palearctic, suggesting that host-pathogen interaction equilibrium has been established.
Keywords: Russia; nos; Chiroptera; Rusko; Humans; Skin; kůže; Mycoses; Haplotypes; Hibernation; lidé; Severní Amerika; Arctic Regions; Evropa; interakce hostitele a patogenu; hibernace; mykózy; Ascomycota; Animals; zvířata; Nose; Europe; North America; Arktida; Host-Pathogen Interactions; haplotypy